2020
DOI: 10.1155/2020/2630827
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Autoimmune Diseases with Type 1 Diabetes Mellitus in Children Depends Also by the Length of Partial Clinical Remission Phase (Honeymoon)

Abstract: Type 1 diabetes mellitus (DM) is characterized by irreversible, autoimmune, pancreatic β-cell destruction. During the disease, some patients experience a phase of Partial Clinical Remission (PCR) known as “honeymoon.” This is a transitory period that is characterized by insulin production by residual β cells following DM diagnosis and initiating the insulin therapy. In this study, we aimed to evaluate the influence of insulin production on immune system after the onset of diabetes, and we showed that the durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 9 publications
3
10
0
Order By: Relevance
“…According to published data the prevalence of thyroiditis is approximately 3-8% and celiac disease ranges from 1 to 10% which is in line with our prevalence study (4% and 5% respectively) [5][6][7].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to published data the prevalence of thyroiditis is approximately 3-8% and celiac disease ranges from 1 to 10% which is in line with our prevalence study (4% and 5% respectively) [5][6][7].…”
Section: Discussionsupporting
confidence: 92%
“…Around the Europe a few studies were published. An Italian study showed that the screening programming for detecting other autoimmune diseases is very critical in the first ten years after the onset of autoimmune diabetes, with 30% prevalence which overlaps with our results [6].…”
Section: Discussionsupporting
confidence: 89%
“…The longest mean duration (26.9 months) was previously described in Turkey [ 40 ]. Recently, a retrospective study showed that patients with a longer duration of PCR seem at risk of developing another autoimmune disease during a 10-year follow-up period after diagnosis [ 41 ]. Our results revealed that age at diagnosis was the only predictor of PCR duration.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a syndrome characterized by decreased insulin secretion and/or tissue insulin sensitivity and altered metabolism of carbohydrates, lipids and proteins, in addition to increased cardiovascular risks (Davis et al., 1996). Type 1 diabetes mellitus (T1DM) is characterized by irreversible and autoimmune pancreatic β ‐cell destruction (Ozen et al., 2020). Type 2 DM (T2DM) is the most incident form, responsible for 90% of the disease prevalence (Wild et al., 2004; World Health Organization, 2006).…”
Section: Introductionmentioning
confidence: 99%